2020
DOI: 10.1093/cercor/bhaa301
|View full text |Cite
|
Sign up to set email alerts
|

Connectivity of the Cingulate Sulcus Visual Area (CSv) in Macaque Monkeys

Abstract: In humans, the posterior cingulate cortex contains an area sensitive to visual cues to self-motion. This cingulate sulcus visual area (CSv) is structurally and functionally connected with several (multi)sensory and (pre)motor areas recruited during locomotion. In nonhuman primates, electrophysiology has shown that the cingulate cortex is also related to spatial navigation. Recently, functional MRI in macaque monkeys identified a cingulate area with similar visual properties to human CSv. In order to bridge the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
22
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(26 citation statements)
references
References 77 publications
(65 reference statements)
4
22
0
Order By: Relevance
“…Somatosensory information, presumably emphasising proprioception, is able to reach mCSv from somatosensory cortex via some combination of PEc, PE, PEci and area 31, and to reach human CSv via a comparable system including hPEc and hPE. Direct input from somatosensory cortex is also suggested by MRI connectivity in both species (Smith et al 2018;De Castro et al 2021). Surprisingly, perhaps, it is more difficult to say how visual and vestibular signals reach CSv.…”
Section: Sources Of Sensory Data For Csvmentioning
confidence: 99%
See 1 more Smart Citation
“…Somatosensory information, presumably emphasising proprioception, is able to reach mCSv from somatosensory cortex via some combination of PEc, PE, PEci and area 31, and to reach human CSv via a comparable system including hPEc and hPE. Direct input from somatosensory cortex is also suggested by MRI connectivity in both species (Smith et al 2018;De Castro et al 2021). Surprisingly, perhaps, it is more difficult to say how visual and vestibular signals reach CSv.…”
Section: Sources Of Sensory Data For Csvmentioning
confidence: 99%
“…Two further multisensory areas to be considered are STP (superior temporal polysensory area) and area 7a. Macaque STP has some connectivity with mCSv in the study of De Castro et al (2021), though this was not mirrored in humans (Smith et al 2018). STP (STPms in human) responds to visual, auditory and tactile stimuli in both macaques (Bruce et al 1981) and humans (Beauchamp et al 2008) but it has no reported vestibular activity and visual motion responses are associated more with object-motion than self-motion (Hietanen and Perrett 1997).…”
Section: Sources Of Sensory Data For Csvmentioning
confidence: 99%
“…On one hand, there is evidence that PCC and RSC directly project to entorhinal and parahippocampal cortices ( Rosene and Van Hoesen, 1977 ; Vogt et al, 1979 ; Insausti et al, 1987 ; Vogt et al, 1987 ; Morecraft et al, 1989 ). On the other hand, these areas are also heavily connected with cortical areas including area 7a ( Pandya et al, 1981 ; Vogt et al, 1987 ; Musil and Olson, 1988 ; Cavada and Goldman-Rakic, 1989 ; Olson and Musil, 1992 ; Shinder and Taube, 2010 ), MSTd ( Akbarian et al, 1994 ; De Castro et al, 2020 ), FEF ( De Castro et al, 2020 ), PIVC, VPS and 3a ( Guldin and Grüsser, 1998 ; De Castro et al, 2020 ). Thus, posterior cingulate region may be one important hub mediating the propagation of self-motion signals from parietal-temporal cortices to the hippocampal-entorhinal system.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, there is a functional link between the left FEF and short-term memory for target locations (Campana et al, 2007;Raabe et al, 2013), as well as a link with visuo-motor integration, requiring for visually guided movements (Wolynski et al, 2009). Research in nonhuman primates further showed that the FEF may be sub-divided into at least two parts (Tian and Lynch, 1996;Petit and Haxby, 1999;Krauzlis, 2004;De Castro et al, 2021): A medial part likely specialized in controlling smooth eye movements (FEFsem) and a lateral part likely specialized in saccadic eye movements (FEFsac). In close exchange with the FEFs are the supplementary eye fields (SEFs).…”
Section: Introductionmentioning
confidence: 99%